PENGARUH EDUKASI TERHADAP PENGETAHUAN MASYARAKAT TENTANG OBAT ANTI TUBERCULOSIS DI PUSKESMAS GEGER - Solihah, Riyadatus; Rahmadani, Rizal (Jurnal Kesehatan Siliwangi, 2024)
TB is a very contagious disease caused by Mycobacterium . Mycobacterium tuberculosis is the most common infection which mostly attacks the lungs. Anti-Tuberculosis Drugs (ATD) are the most important component in the treatment of tuberculosis. Tuberculosis treatment is one of the most efficient to prevent the further spread of tuberculosis and include antibiotic drugs which function in various ways to kill tuberculosis bacteria. The purpose of study is to determine the effect of education about Anti-Tuberculosis Drugs (ATD) on public knowledge at the Geger Health Center. This research used observational analytics using a cross sectional approach, the population was 78 respondents with a sample of 65 respondents. The sampling technique was non-probability sampling with the purposive sampling method. The research was conducted at the Geger health center in April 2024. The data collection used questionnaires. Data analysis was univariate and bivariate using the paired t-test. The results of the research before being given education (pretest) 30 (46.2%) respondents were in the poor category, while after given education (posttest) 53 (81.5%) were in the good category. Based on the results of statistical using t-test, the p-value (0.000) < α (0.05) was obtained, which means there was an effect of education on public knowledge about anti-tuberculosis drugs at Geger health centers. It was concluded that there was an increase in public knowledge about anti-tuberculosis drugs at Geger health centers after being given education. The suggestion for future researchers is to add variables that can influence the attitude of Tuberculosis patients towards treatment.